Making sense of response: How policies affect climate vulnerability - Malmström, Alexandra; Käyhkö, Janina; Räsänen, Aleksi; Tuomimaa, Julia; Juhola, Sirkku (Springer Nature, 2025)
There is a gap in understanding how different policies affect climate vulnerability and risk development, yet increasingly response is added to the risk framework. We propose a conceptual framework that explains how response and other policies affect risk determinants and demonstrate the application of the framework using a synthesis of empirical literature on climate-related health risks and adaptation in cities. The analysis shows that most of the policies affecting vulnerability and exposure are outside climate interventions, i.e., current conceptualization of response. The inclusion of response and other policies in risk assessments has implications for adaptation research and practice.
Keywords: vulnerability; response; adaptation; Climate justice; Climate risk